2015
DOI: 10.1182/blood.v126.23.1455.1455
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of CXCR4 Impairs Anti-CD20 Monoclonal Antibody (Rituximab)-Dependent Cytotoxicity in Diffuse Large B-Cell Lymphoma

Abstract: Introduction: Diffuse large B-cell lymphoma (DLBCL) is the most common form of B-cell-derived non-Hodgkin lymphoma, with a varying response and long-term outcome following therapy. The anti-CD20 monoclonal antibody rituximab has improved the survival outcome of DLBCL patients significantly. However, refractory and recurrent disease are major clinical problems due to drug-specific molecular resistance in this heterogeneous disease and patients with early relapse after rituximab-containing first-line therapy hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…8 Interestingly, CXCR4 + DLBCL cell lines show resistance to rituximab but are sensitive to the combination of rituximab with a CXCR4 antagonist. 14,15 Most importantly, we and others reported that CXCR4 overexpression associates with poor progression-free and overall survival in DLBCL patients treated with R-CHOP. 7,8,14 Our group has developed T22-GFP-H6, a self-assembling protein nanocarrier, which uses the peptidic T22 ligand to target the CXCR4 receptor.…”
Section: Ferrata Storti Foundationmentioning
confidence: 81%
See 1 more Smart Citation
“…8 Interestingly, CXCR4 + DLBCL cell lines show resistance to rituximab but are sensitive to the combination of rituximab with a CXCR4 antagonist. 14,15 Most importantly, we and others reported that CXCR4 overexpression associates with poor progression-free and overall survival in DLBCL patients treated with R-CHOP. 7,8,14 Our group has developed T22-GFP-H6, a self-assembling protein nanocarrier, which uses the peptidic T22 ligand to target the CXCR4 receptor.…”
Section: Ferrata Storti Foundationmentioning
confidence: 81%
“…14,15 Most importantly, we and others reported that CXCR4 overexpression associates with poor progression-free and overall survival in DLBCL patients treated with R-CHOP. 7,8,14 Our group has developed T22-GFP-H6, a self-assembling protein nanocarrier, which uses the peptidic T22 ligand to target the CXCR4 receptor. 16 This carrier displays a high recirculation time in blood and selectively biodistributes to tumor tissues in solid tumor models, internalizing selectively in CXCR4 + cancer cells, while increasing its tumor uptake compared to the untargeted GFP-H6 counterpart.…”
Section: Ferrata Storti Foundationmentioning
confidence: 81%